Goodbye to yesterday [compact disc, unabridged] - Brunstetter, Wanda E. (Brunstetter, Wanda E. Discovery, 2013)
Instead of experiencing newlywed bliss, Meredith and Luke Stoltzfus are faced with the greatest challenge of their young lives.